2020
DOI: 10.1097/mlr.0000000000001284
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Peer Specialist Services on Residential Stability and Behavioral Health Status Among Formerly Homeless Veterans With Cooccurring Mental Health and Substance Use Conditions

Abstract: Objectives: This study tested the impacts of peer specialists on housing stability, substance abuse, and mental health status for previously homeless Veterans with cooccurring mental health issues and substance abuse. Methods: Veterans living in the US Housing and Urban Development—Veterans Administration Supported Housing (HUD-VASH) program were randomized to peer specialist services that worked independently from HUD-VASH case managers (ie, not part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…One randomised controlled trial (Corrigan et al, 2017) examined an ethnically matched peer-navigator programme compared to the usual care among homeless African Americans with serious mental illness and measured psychological distress using the Texas Christian University Health Forms (TCU-HF). Investigators found that those in the intervention group reported better im- Conversely, one randomised controlled trial (Ellison et al, 2020) examined a peer-specialist intervention compared to usual care among homeless veterans receiving housing vouchers and measured symptoms of mental illness using the 24-item Behaviour And Symptom Identification Scale (BASIS-24) up to 12 months and found no statistically significant between-group difference (p > .05). Another randomised controlled trial (Nyamathi et al, 2001) examined an ethnically matched female peer-mentorship programme compared to usual care among homeless women and their intimate partners, measuring psychological well-being over 6 months using the Mental Health Index (MHI-5) and found no statistically significant improvement among those receiving peer support compared to the usual care (Regression coefficient B = −5.17 (SE 2.2); p = .019).…”
Section: Outcomes 2: Mental Healthmentioning
confidence: 99%
“…One randomised controlled trial (Corrigan et al, 2017) examined an ethnically matched peer-navigator programme compared to the usual care among homeless African Americans with serious mental illness and measured psychological distress using the Texas Christian University Health Forms (TCU-HF). Investigators found that those in the intervention group reported better im- Conversely, one randomised controlled trial (Ellison et al, 2020) examined a peer-specialist intervention compared to usual care among homeless veterans receiving housing vouchers and measured symptoms of mental illness using the 24-item Behaviour And Symptom Identification Scale (BASIS-24) up to 12 months and found no statistically significant between-group difference (p > .05). Another randomised controlled trial (Nyamathi et al, 2001) examined an ethnically matched female peer-mentorship programme compared to usual care among homeless women and their intimate partners, measuring psychological well-being over 6 months using the Mental Health Index (MHI-5) and found no statistically significant improvement among those receiving peer support compared to the usual care (Regression coefficient B = −5.17 (SE 2.2); p = .019).…”
Section: Outcomes 2: Mental Healthmentioning
confidence: 99%
“…Service episodes were then counted for the 3 months before study enrollment and for the 9 months after enrollment—when most participants completed the project (some continued to receive services for another 3 mo due to interruptions in their period of service caused by peer specialist turnover). 24 …”
Section: Methodsmentioning
confidence: 99%
“…17−30 Study participants comprised a majority sample of White (15 studies) 18,22,24−36 male individuals (15 studies), 19,22,23,25 −30,33−35,37−39 with a mean age of 45 years (age range = 30.6−55.3 years) who were single, divorced, or never married (6 studies). 19,23,28,31,37,38 Nonspecified serious mental illness (12 studies), [17][18][19][20][21]23,27,28,31,32,35,36 depression (11 studies), 17,[20][21][22]24,[31][32][33]35,37,39 schizophrenia/ schizoaffective disorder (11 studies), 17,20,21,23,27, 31,32,35 −37,39 and SUD (11 studies) 18,19,23,[25][26][27][29][30][31]34,38 were the most prevalent behavioral health conditions experienced by the study participants. Other frequently observed behavioral health conditions were bipolar disorder (8 studies) 17,20,…”
Section: (Available Online)mentioning
confidence: 99%
“…21,24,25,31,35 In addition, 11 studies focused on populations previously having received or currently receiving inpatient care or hospitalization for a mental health or SUD, 18,23,27,28,[31][32][33]35,36,38,39 and 6 focused on individuals previously having or currently experiencing homelessness. 19,26,27,29,37,38 A majority ( 16) of studies included participants receiving usual care as a control. [17][18][19][20][21][22][23][24]26,28,[30][31][32]35,37,38 Within the context of this review, usual care refers to a continuation of nonpeer-provided medical or behavioral health services received before study enrollment that includes outpatient psychotherapy, rehabilitation services, and case management.…”
Section: (Available Online)mentioning
confidence: 99%
See 1 more Smart Citation